Análise comparativa da infiltração marginal apical de três cimentos endodônticos através de um processo de diafanização - Villela, Alexandre Mascarenhas (2007)
The success of endodontic treatment is directly related to proper execution all its phases, from diagnosis to your proservation. The filling of the system root canal is no exception to this rule and deserves special attention because it is the phase that ends the treatment itself. The filling material should seal the entire system root canal space formerly occupied by the root pulp, promoting a sealing airtight and three-dimensional. Over the years various materials have been tested, however, Currently the use of gutta-percha (solid material) associated with a sealer (Plastic) is almost unanimous. The gutta-percha should be the main material shutter and must occupy the greatest possible proportion of the light of the root canal system. However, sealers have shown to influence, directly, the endodontic treatment success. Numerous studies have been and are still being held in trying to develop a concrete covering all the physical and chemical characteristics and biological a filling material. This study aimed to evaluate compared the ability of apical sealing of cement: Sealer 26®, Acroseal® and EndoREZ®. All experiments were conducted at the Research Laboratory of Endodontics, School of Dentistry, State University of Rio de Janeiro. It was concluded that none of the tested cements was able to prevent marginal leakage Apical in all tested teeth. After statistical analysis, the Sealer 26® cement and cement Acroseal® no statistically significant differences, contrary to cement EndoREZ® which showed a much lower and statistically significant